2020
DOI: 10.3390/w12061724
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Approaches for Determining Dripline Depth and Irrigation Frequency of Subsurface Drip Irrigated Rice on Different Soil Textures

Abstract: Water saving techniques such as drip irrigation are important for rice (Oriza sativa L.) production in some areas. Subsurface drip irrigation (SDI) is a promising alternative for intensive cropping since surface drip irrigation (DI) requires a higher degree of labor to allow the use of machinery. However, the semi-aquatic nature of rice plants and their shallow root system could pose some limitations. A major design issue when using SDI is to select the dripline depth to create appropriate root wetting pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Shakhali et al [15] used HYDRUS-2D to simulate changes in volumetric soil water contents (VWCs) underline sources with different irrigation water salinities and reported an excellent performance of the model compared with field observations. Arbat et al [16] also confirmed the reliability of the model to assess soil water dynamics, such as deep drainage and plant water uptake for various dripline depths, soil types, and irrigation schedules. Honari et al [17] also reported high accuracy of the 3D model in modeling soil water dynamics under subsurface drip irrigation.…”
Section: Introductionmentioning
confidence: 78%
“…Shakhali et al [15] used HYDRUS-2D to simulate changes in volumetric soil water contents (VWCs) underline sources with different irrigation water salinities and reported an excellent performance of the model compared with field observations. Arbat et al [16] also confirmed the reliability of the model to assess soil water dynamics, such as deep drainage and plant water uptake for various dripline depths, soil types, and irrigation schedules. Honari et al [17] also reported high accuracy of the 3D model in modeling soil water dynamics under subsurface drip irrigation.…”
Section: Introductionmentioning
confidence: 78%
“…The influencing factors of the soil water during channel infiltration include the soil texture, channel form and channel cross‐sectional area. Arbat et al (2020) successfully verified the influence of the soil texture on the soil moisture dynamics by performing simulations using the HYDRUS‐2D software. Montaseri proved that numerical simulation studies on the sediment transport and channel form can describe the soil moisture and particle movement mechanisms Montaseri et al (2020).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous foreign and domestic studies of the cultivation of both dry and aerobic rice show [1][2][3][4][5][6][7][8] that the issue of transition from flooded rice to aerobic rice is relevant and should be worked out in accordance with all modern ecological and reclamation requirements that are currently imposed on production agricultural products, including rice culture [9,12]. High interest among rice producers, as a rule, is associated with the further impossibility and/or inefficiency of rice production using the traditional technology of rice cultivation with continuous or shortened flooding of rice paddies due to the lack or insufficiency of the required volume and / or quality of irrigation water, lack of the necessary technical support for the implementation of all agrotechnical methods necessary for the normal cultivation of rice, reducing the soil reclamation state to a level at which the introduction of organic and mineral fertilizers does not compensate for the low soil fertility and is ineffective and economically inexpedient [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%